Coffee agrotourism development strategy in Belok Sidan Village, Petang District, Badung Regency - Ketut, Ketut Sumantra; Desak Made Mas Swandewi; I GD. Yudha Pratama; I K. Widnyana (International Journal of Applied Sciences in Tourism and Events, 2023)
The study was aimed to determine the strategy for developing coffee agro-tourism in Belok Village, Petang District, Badung Regency. The method used is a qualitative method with interviews, which are then analyzed using SWOT analysis by evaluating strengths and weaknesses as internal factors, opportunities and threats as external factors, and using the AHP (Analytical Hierarchy Process) method to calculate the priority weight of the criteria considered. The support from the private sector in developing tourism villages plays a significant role in the development of Belok Sidan Village (strength), the lack of supporting facilities for agro-tourism activities (weakness), the number of tourism workers returning to the village and entrepreneurial factors through MSMEs can play a role in diversifying people's livelihoods (opportunity). Natural disasters/disorders (threats) are a significant factor in developing coffee plantation-based agro-tourism in Belok Sidan Village. Belok Sidan village coffee agro-tourism has the potential as a coffee farming area that can support the eco-nomic structure of Badung Regency. Based on the IFAS and EFAS matrix score analysis, the alternative strate-gies used in developing Belok Sidan village coffee agro-tourism are developing creative economy businesses, agro-tourism digitalization, and Agro Techno Park. According to the AHP analysis results, the Agro Techno Park development is the priority strategy.